Sistem Informasi Penjualan Berbasis Website dengan Pendekatan Metode Prototype - Arief Ichwani; Nizirwan Anwar; Kundang Karsono; Mohamad Alrifqi (Ikatan Ahli Informatika Indonesia, 2021)
Kinov Seprai is a business that has been operating for four years focusing on selling sheets and mattress covers, the system used by Kinov Seprai is still uses the manual method for recording sales data and product data, product marketing is limited to the surrounding area and is carried out by word of mouth. , product orders must come to the location so that the number of sales is limited and prone to human error. Web-based information system is a technology that contains various information, transactions and data processing to overcome these problems. The method used to build an information system is a prototype and problem analysis using the PIECES method. The results of this study are web-based information systems can provide informative information, effective promotional media, wider target market and easier and time-saving sales services.